Alliances to Acquisitions: A Road Map to Advance the Field of Strategic Management - Zakaria, Rimi; Genç, Omer Faruk (Emerald Group Publishing Ltd. Howard House Wagon Lane, Bingley BD16 1WA, 2017)
Although primarily treated as two distinct research streams, strategic alliances and mergers and acquisitions together occupy much of the strategic management discourse. Alliances, in many cases, end in acquisitions as firms use alliances as intermediate strategic options to eventually acquire a partner. As the discipline of strategy matures and the frequency and the volume of inter-firm cooperation continue to rise, it is imperative to integrate these two research streams for a holistic understanding of the theory of the firm. The purpose of this conceptual piece is threefold. First, we review the extant studies that combine these two governance modes: alliance and acquisitions. Second, drawing on the dominant strategic management theories, we highlight how prior inter-firm alliances inform future acquisitions in terms of (a) pre-combination decisions, (b) post-deal integration processes, (c) alternatives and strategies, and (d) performance outcomes. Finally, in view of the emerging trends and evocative gaps, we offer a conceptual road map to encourage future theoretical development and empirical research. © 2017 Elsevier B.V., All rights reserved.
Keywords: Behavioral Theory; Mergers and Acquisitions; Network Theory; Real Options Theory; Resource-Based View; Strategic Alliances; Transaction Cost Economics